The Effect Of Varied Kicking Training On Shooting Skills In Futsal Games For Extracurricular Players Of The Dehasen University Of Bengkulu Women's Student Association - Rahmalia, Khotimah; Febrianti, Mariska; Perdima, Feby Elra (Universitas Dehasen Bengkulu, 2026)
This study aims to determine the effect of kicking variation training on shooting skills in futsal games on female extracurricular himajas players at Dehasen University, Bengkulu. This type of research is experimental research with a sample of 20 players. The results of the study showed that there was a significant effect of the influence of kicking variation training to various targets in developing the shooting skills of futsal players in the female himajas futsal extracurricular. The results were stated in the calculated t value of 4.35 and t table (0.05) (19) 2.093, and a significance value of 0.000 <0.05, and a percentage increase of 27%, so Ha was accepted. The shooting pretest data of female himajas futsal extracurricular players in the very poor category were 3 players with a percentage of 15%, the poor category were 14 players with a percentage of 70% and the moderate category were 3 players with a percentage of 15% and in the good and very good categories there were no players who got this category. Then the posttest shooting data was obtained for the Himajas female futsal extracurricular players in the very poor category with a percentage of 5%, the poor category with a percentage of 5% and the moderate category with a percentage of 9 players with a percentage of 45% and in the good category with a percentage of 5 players with a percentage of 25% and there were no players in this category who were very good.